Indicators for an ecosystem approach to the management of fisheries and the marine environment in West Africa waters [résumé] - (:unkn) unknown (My University, 2017)
Several activities have been conducted on the thematic of « ecosystem indicators, sensu lato» during the AWA project (www.awa-project.org). This communication reports those related to the Tasks 3 of the WP4. Its first part introduces the indiAWA network which has emerged as a result of the AWA project. IndiAWA is a research and expertise network focussing on indicators and ecosystem approaches for fisheries and global change in West Africa. Started in the AWA context, IndiAWA has the ambition to continue on the long term, after AWA phase 1 funding period, as well as to be an open network, with the addition of extra AWA contributors, and to constitute a growing task force for West Africa. With AWA's consortium and extended collaborations, the general and long-term objective of indiAWA is to develop ecosystem indicators and to promote regional solutions for an Ecosystem Approach to the management of fisheries and the marine environment in West Africa waters. In line with AWA's philosophy, this long-term objective of indiAWA comes in three main components, including scientific research, capacity building and communication objectives. These components are presented and their sub-components or particular objectives are specified in the first part of the communication. The second part brings then an illustration of the indiAWA's approach applied to the Guinean shelf case study. In this study, the ecosystem indicators calculated on the basis on three decades of national scientific trawling surveys, coupled with others indicators from commercial fishing activities on the same period, allows now to detect some of the fisheries ecosystem effects that were not perceptibles in former studies, based on both shorter data series and period of exploitation. The third and last part of the communication concludes with some perpectives and work to be continued and developped on this thematic on the future by the AWA/indiAWA consortium.
Keywords: African Research